Unraveling Natural Products' Role in Osteoarthritis Management-An Overview - Georgia-Eirini Deligiannidou; Rafail-Efraim Papadopoulos; Christos Kontogiorgis; Anastasia Detsi; Eugenia Bezirtzoglou; Theodoros Constantinides (MDPI AG, 2020)
The natural process of aging gradually causes changes in living organisms, leading to the deterioration of organs, tissues, and cells. In the case of osteoarthritis (OA), the degradation of cartilage is a result of both mechanical stress and biochemical factors. Natural products have already been evaluated for their potential role in the prevention and treatment of OA, providing a safe and effective adjunctive therapeutic approach. This review aimed to assess the therapeutic potential of natural products and their derivatives in osteoarthritis via a systematic search of literature after 2008, including in vitro, in vivo, ex vivo, and animal models, along with clinical trials and meta-analysis. Overall, 170 papers were obtained and screened. Here, we presented findings referring to the preventative and therapeutic potential of 17 natural products and 14 naturally occurring compounds, underlining, when available, the mechanisms implicated. The nature of OA calls to initially focus on the management of symptoms, and, in that context, several naturally occurring compounds have been utilized. Underlying a global need for more sustainable natural sources for treatment, the evidence supporting their chondroprotective potential is still building up. However, arriving at that kind of solution requires more clinical research, targeting the implications of long-term treatment, adverse effects, and epigenetic implications.